The identity of Withania kansuensis (Solanaceae): insight from trichome morphology - Wang, Jinxiu; Niu, Guohao; Liu, Yifan; Chen, Xiyang (Phytotaxa, 2026)
Withania kansuensis was treated as a synonym of W. somnifera in Flora of China, although it was suggested to be a possible distinct species by its reported simple (vs. dendritic in W. somnifera) trichomes. In the present study, we examined the trichome morphology of both taxa and identified a continuous series of five types, including intermediate forms between simple and dendritic trichome. This demonstrates a continuous morphological variation in trichomes between the two taxa. Our findings therefore support that W. kansuensis is conspecific with W. somnifera.